(untitled) (Bangladesh Medical Journal Khulna, 2012)
Jejunogastric intussusception (JGI) is a rare but serious complication following gastrojenjunostomy operation. Clinical presentation may be acute or chronic. The efferent loop intussusception is most frequent type. Our case report include a 60 years male presented with sudden onset of epigastric pain, vomiting, hematemesis and a palpable mass at epigastrium with previous history of gastric surgery about 11 years back. Diagnosis of JGI was confirmed with endoscopy findings. After prompt resuscitation early surgery was done. Gangrenous segment was resected and revision surgery was done in Roux-en-Y pattern. Post-operative period was uneventful. Awareness of such complication, early diagnosis and prompt surgery can reduce the mortality of JGI. DOI: http://dx.doi.org/10.3329/bmjk.v43i1-2.13018 Bang Med J (Khulna) 2010; 43: 18-20